1997
DOI: 10.1159/000099885
|View full text |Cite
|
Sign up to set email alerts
|

Selective Dorsal Rhizotomy in Children with Cerebral Palsy

Abstract: Objective: Effects of selective dorsal rhizotomy (SDR) were studied in children with spastic cerebral palsy in orthopaedic and functional fields. Methods: In a prospective study, we compared the same population before SDR and 1 year after SDR. This population included children with spastic cerebral palsy, when spasticity was responsible for a halt in the motor skill acquisitions or for orthopaedic complications. All the children had intensive physiotherapy for 6 months postoperatively. We observed spasticity b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0
4

Year Published

2001
2001
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 0 publications
0
28
0
4
Order By: Relevance
“…Chan et al concluded that SDR had a neutral effect when 90% of those with preoperative hip subluxation continued to do so postoperatively, and 88% of those with typically developing hips preoperatively remained normal. Similarly, Hodgkinson et al reported no evolution of hip migration but that SDR did not have a preventative effect. A small case series reported rapid progression in five non‐ambulatory patients …”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Chan et al concluded that SDR had a neutral effect when 90% of those with preoperative hip subluxation continued to do so postoperatively, and 88% of those with typically developing hips preoperatively remained normal. Similarly, Hodgkinson et al reported no evolution of hip migration but that SDR did not have a preventative effect. A small case series reported rapid progression in five non‐ambulatory patients …”
Section: Resultsmentioning
confidence: 94%
“…Four non‐English language publications that addressed the study question were excluded. After full‐text review, 23 papers remained . A search of the reference lists of these articles and key articles on hip displacement identified one additional article (Greene et al).…”
Section: Resultsmentioning
confidence: 99%
“…It has shown significant reduction in spasticity in children, although the outcomes may be variable, and orthopedic complications, such as subluxation of the hips, may not be prevented. 47,48 A study by Oki et al 49 concluded that all the pediatric participants with spastic hemiparesis included in the study had a reduction of tone after SDR, as measured by a modified Ashworth scale, and showed an improvement in gait. Many adults who had SDR as children highly recommend the procedure as well.…”
Section: Treatmentsmentioning
confidence: 99%
“…77,81 There has been a trend toward relying less on the electrophysiological responses and more on the clinical findings, and in many centers a combination of the two is used. 37,[48][49][50]79,87 However, in only two of the three RCTs was the improvement in GMFM scores statistically more than in a control group receiving physiotherapy only. 74 There is very strong evidence that SDR results in improvements in lower-limb spasticity and an increase in the range of movement at the lower-limb joints with no loss of strength.…”
Section: Neurosurgical Procedures Directed At Spasticitymentioning
confidence: 87%
“…[35][36][37]59 The surgical procedure for SDR is performed either at the level of the conus via one-or two-level laminectomies, or at the level of the root exit foramina via multilevel laminectomies or laminotomies, with replacement of the laminar flap. With respect to this complication, fewer than 20% of patients worsened and the vast majority were stable (43-80%) or actually showed improvement (9-38%) in the amount of hip subluxation after SDR.…”
Section: Neurosurgical Procedures Directed At Spasticitymentioning
confidence: 99%